Adaptation Of Sunflowers To Salinity Stress On Coastal Land - Silvia Permata sari; Obel Obel; Elara Resigia; Winda Purnama Sari Purnama Sari; Jamsari Jamsari; Ali Rahmad; Seswita Seswita (JURNAL AGRONOMI TANAMAN TROPIKA (JUATIKA), 2022)
Sunflower is one of the oil-producing plants that potentially can be developed as a food raw material, industrial, medicine, and cosmetics. Sunflower cultivation needs to be conducted in various lands in Indonesia; one of them is coastal regions. However, on one side, these lands were included on marginal land because the high level of salinity constrains it. This research aims to determine sunflower growth and thrive on salinity stress in the coastal land. This research applies a random group design with five treatments consisting of two accession and three sunflower varieties with three repetitions. The research result shows that the sunflower accession Ha1 growth and thrive on salinity stress in coastal land was quite significant compared to the accession Ha15 and Kanigara, Helina IPB, and BM1 IPB varieties. Generally, sunflower can adapt to stress salinity in coastal land.